Workload and Performance of Nurses During The Covid-19 Pandemic: A Meta Analysis Study - Gde Palguna Reganata; I Gusti Ngurah Made Yudhi Saputra (Universitas Bumigora, 2022)
The surge in Covid-19 cases has caused hospitals and health workers to experience functional collapse. The high workload in handling Covid-19 cases by nurses is happening everywhere. Many studies have been conducted to look at the effect of workload on nurse performance during a pandemic. This research was conducted to determine the effect of workload on the performance of nurses with a meta- analysis approach. This type of research is observational with a retrospective approach. This research conducted through secondary data obtained from relevant sources related to the workload of nurses and nurse performance in various journals. The population and samples were taken from studies that met the criteria. Data analysis using meta-analysis. The result showed that there is a negative correlation between workload and performance of nurses, with ρ= 0 .334 are in the reception area of the 95% (0.334±0.219) confidence interval with p-value < 0.0001. Workload has a contradictory effect on performance, where when the workload of nurses is high, nurses tend to experience a decrease in performance. This needs to be a serious concern, because nurses are at the forefront of health services. If the nurse’s performance has started to decline, then the patient’s handling becomes not optimal and can increase the risk of death for the patient.